2012
DOI: 10.1016/j.sysconle.2011.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Diagonal Riccati stability and positive time-delay systems

Abstract: We consider a class of algebraic Riccati equations arising in the study of positive linear time-delay systems. We show that this class admits diagonal positive definite solutions. This implies that exponentially stable positive linear timedelay systems possess Lyapunpov-Krasovskii functionals of a simple quadratic form. We also show that for this class of equations, the existence of positivedefinite solutions is equivalent to a simple spectral condition on the coefficient matrices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…The above result provides a solution to this problem for the particular cases of linear positive and positively dominated systems with delays. Note that the positive systems case has also been solved in [51,32] using different approaches. These results have since been extended to some other classes of systems in [67].…”
Section: Proposition 13mentioning
confidence: 99%
See 1 more Smart Citation
“…The above result provides a solution to this problem for the particular cases of linear positive and positively dominated systems with delays. Note that the positive systems case has also been solved in [51,32] using different approaches. These results have since been extended to some other classes of systems in [67].…”
Section: Proposition 13mentioning
confidence: 99%
“…(iii) A linear positive system with constant discrete delay is stable if and only if the associated Riccati equation has diagonal solutions [32,51].…”
Section: Introductionmentioning
confidence: 99%
“…So, it is of high importance to calculate analytic or numerical approximate for it. In recent decades, some new numerical and analytic approximate methods have been proposed for solving such a difficult problem in the context of delay ordinary differential equations (see for example [31][32][33][34][35][36][37]). To overcome this difficulty, an iterative approach, based on the VIM, will be introduced in the next section.…”
Section: (24)mentioning
confidence: 99%
“…This established the existence of a diagonal Lyapunov functional for asymptotically stable positive linear time-delay systems, providing a natural extension of a fundamental property of positive linear time-invariant (LTI) systems [2]. Furthermore, this fact strengthened the main result of [5] which showed that under the same condition (A + B Hurwitz), there exists a diagonal P ≻ 0 and Q ≻ 0 (not necessarily diagonal) satisfying (1).…”
Section: Background and Introductionmentioning
confidence: 65%